RECONSTRUCTING THE SCIENCE LEARNING MATERIAL CONTAINING NATURE OF ‎SCIENCE ON THE TOPIC OF GLOBAL WARMING AND CLIMATE CHANGE - yulius lumban tobing; Ahmad Mudzakir (EDUSAINS, 2017)
The purpose of this study was to obtain a pre-conception of learners and scientists perspective on the concept of climate change, global warming and relations between them; know the characteristics of teaching materials; and find an expert assessment of the design of instructional materials. The method used in this study is a mixed methods using sequential eksploratorisdesign by adapting the Model of Educational Reconstruction(MER). Instruments are interview form, text analysis sheet, validation indicators sheet and cognitive aspects of learning objectives and affective aspects, validation concept analysis sheet, validation design teaching materials sheet, readability test and scientific literacy test. Results of interviews to 10 junior high school students showed a pre-conception of learners with different perspectives of scientists on global warming and climate change. Characteristics of teaching material produced are (a) developed accordance reflection of learners pre-conceptions and the scientist's perspective (b) accessible, (c) equipped with aspects of nature of science (NOS), and (d) using a sequence of teaching and learning of Science and Technology Literacy (STL) by adopting a learning phase Chemie im a Context (ChiK). The results of the validation of teaching materials to obtain an average value of CVI is 0,99. Results of the questionnaire responses obtain an average value of 4.46, while the test results showed therewere also significantly differences in the value of literacy students between before with after studying the teaching materials (p=0,00). Keywords: Teaching Material; Nature of Science; and Model of Educational Reconstruction